The Law On Human Trafficking For The Purpose Of Illegal Organ Trade - Hasudungan Sinaga (Ridwan Institute, 2023)
The merits and drawbacks of organ sales are vigorously debated in Indonesia. Nevertheless, some argue that the trade in human organs should be prohibited, a stance supported by Indonesian law. Both organ recipients and donors bear significant responsibility in organ trade, as financial gain serves as the primary motive for organ brokers and medical professionals alike. This research aims to conduct a Legal Analysis of Human Trafficking for the Purpose of Organ Illegal Trade. The methodology employed is a literature review through online searches on various journal platforms such as Google Scholar, Science Direct, and the Garuda Portal, focusing on national and international scientific journal articles. The search, limited to the last four years (2019-2023), employed subject-specific terms like